PERAN GURU DALAM MEWUJUDKAN TUJUAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Tatang Hidayat; Makhmud Syafe’i (Rayah Al-Islam, 2018)
The purpose of this study is to determine the role of teachers in realizing the objectives of Islamic Religious Education learning in schools. This present study employed a qualitative approach in the form of literature study. Based on the results of the study, the learning objectives of Islamic Religious Education were easily featured by the integration between the life of the world and the hereafter. Therefore, the Islamic Religious Education learning plans should be formulated in a different method compared to other subjects. In the learning processes of Islamic Religious Education, teachers were highly encouraged to be skillful in developing learning materials and methods. Accordingly, as the role of teachers, they were firstly encouraged to understand the pedagogical competence. Based on the material aspects, teachers were encouraged to have ability in developing Islamic Religious Education materials not only in the realms of cognitive understanding but also in the realms of practical good deeds. In addition, based on the methodological aspects, teachers were encouraged to courageously utilize Islamic education methods, such as the methods of Quranic education, riyadhah, rihlah, talaqi, halaqah, and many more. With respect to the learning evaluation, teachers were encouraged to assess the aspects of the attitudes and skills of students on a daily basis in practicing Islamic teachings since it is obvious that the essence of the objectives of learning Islamic Religious Education was to realize faithful, knowledgeable, and pious students.